2015
DOI: 10.1007/s40615-015-0111-1
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Health and Health Care: an Assessment and Analysis of the Awareness and Perceptions of Public Health Workers Implementing a Statewide Community Transformation Grant in Texas

Abstract: Among public health workers, recent exposure to information regarding health disparities may be associated with their perceptions of health disparities. Further research is needed to investigate the impact of such exposure on their long-term perception of disparities, as well as the equity of services and programs they administer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We live in a time of unprecedented health transformation. Health disparities of all types (rural, age, race, and gender) are steady, if not increasing, and for the first time in US history, overall life expectancy is declining 15. Climate change,68 opioid misuse and addiction,911 integration of physical and behavioral health,1215 and persistent rates of chronic disease are both contemporary and emerging public health problems.…”
mentioning
confidence: 99%
“…We live in a time of unprecedented health transformation. Health disparities of all types (rural, age, race, and gender) are steady, if not increasing, and for the first time in US history, overall life expectancy is declining 15. Climate change,68 opioid misuse and addiction,911 integration of physical and behavioral health,1215 and persistent rates of chronic disease are both contemporary and emerging public health problems.…”
mentioning
confidence: 99%
“…A recent screening of banked sera from Cameron County, Texas revealed that 0.36% of residents had a confirmed Chagas disease infection [12]. With each colonia having different and unique social determinants of health [17], our current study aimed to continue surveillance in neighboring Starr County and to further understand the Chagas disease prevalence and risk factors for infection in this local population.…”
Section: Introductionmentioning
confidence: 99%